NUMERICAL ANALYSIS STUDY OF THE EFFECT GEOPOLYMER CONCRETE COMPRESSIVE STRENGTH ON DUCTILITY OF REINFORCED CONCRETE BEAMS - Muhammad Wildan Aziz; Priyo Suprobo; Yuyun Tajunnisa (Institut Teknologi Sepuluh Nopember (ITS), 2022)
Geopolymer concrete that has polymer formwork is very likely to be used as reinforced concrete material with several advantages. The advantages of geopolymer concrete when compared to portland cement concrete are: resistant to acidic environments (corrosion resistance), better bond strength of reinforcement with concrete material, stable at high temperatures, higher fracture energy. Previous experimental studies found that the tensile strength, bond strength, and fracture energy of geopolymer concrete were better, leading to the hypothesis that the ductility value of geopolymer concrete was better than portland cement concrete. The identification of ductility values based on the compressive strength of concrete will be carried out in research using the finite element method using the 3D ATENA program. Several specimens with compressive strength of 25 MPa, 30 MPa, 35 MPa, 40 MPa, and 45 MPa were compared with their ductility values. The results showed that the 25 MPa specimen had the highest ductility value with 5.33, while the lowest ductility value is 45 MPa specimen with 3.39.